Size structure of Olive Ridley turtle Lepidochelys olivacea (Testudines: Cheloniidae) in Tumbes, Peru - Vera, Manuel (2012)
In this paper we analyzed the size structure of Olive Ridley turtle Lepidochelys olivacea, from individuals stranded and incidentally caught in beaches of Tumbes, Peru (3º38’9.5”S – 80º36’2.48”W; 3º57’21.3”S – 80º57’45.72”W), since November 2006 to October 2011. The study area was divided into three contiguous areas, which were limited by the most active streams (Bocapan, El Rubio and Peña Negra). There were 39 individuals (74.4% stranded and 25.6% caught incidentally), with sizes ranged from 45 to 75 cm CCL (62.5±5.7 cm CCL). 64.1% was considered sub-adult individuals (<65 cm CCL, n= 25). Spatially the largest number of records occurred in zones 3 and 2, in which percentages above 60% were considered sub-adults, while in zone 1, 83% was adult. Temporarily in the rainy season were registered the majority of the observations (59%), in which 78.3% of specimens was sub-adult, being higher than in the dry season (43.8%). Sizes showed significant differences between zones and climatic seasons. It was confirmed the latitudinal distribution pattern by apparent maturity stages (more adults in the north). Adults’ occurrences suggest that Tumbes coast would be a potential nesting area of L. olivacea, most likely to oviposit in dry season, it which is supported by recent nesting events.